2005
DOI: 10.1242/jcs.02527
|View full text |Cite
|
Sign up to set email alerts
|

A novel dileucine lysosomal-sorting-signal mediates intracellular EGF-receptor retention independently of protein ubiquitylation

Abstract: One of the main goals of this study was to understand the relationship between an epidermal growth factor (EGF) receptor dileucine (LL)-motif (679-LL) required for lysosomal sorting and the protein ubiquitin ligase CBL. We show that receptors containing 679-AA (di-alanine) substitutions that are defective for ligand-induced degradation nevertheless bind CBL and undergo reversible protein ubiquitylation similar to wild-type receptors. We also demonstrate that 679-LL but not CBL is required for EGF receptor down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…It has been documented that GGAs display a critical function in packaging of mannose-6-phosphate receptors into clathrin-coated vesicls in the TGN, which could be regulated by the phosphorylation state of GGAs (131, 186, 189). Thus, to ascertain the function of dileucine-based signals in relation to [D/E]XXXL [L/I] or DXXXL motifs, it should be emphasized that the former are recognized by heterotetrameric adaptor complexes such as AP-1, AP-2, AP-3, and AP-4, which later bind GGA adaptor proteins (4, 147, 148, 190192). …”
Section: Modulation Of Receptor Trafficking and Sequestration By Smentioning
confidence: 99%
“…It has been documented that GGAs display a critical function in packaging of mannose-6-phosphate receptors into clathrin-coated vesicls in the TGN, which could be regulated by the phosphorylation state of GGAs (131, 186, 189). Thus, to ascertain the function of dileucine-based signals in relation to [D/E]XXXL [L/I] or DXXXL motifs, it should be emphasized that the former are recognized by heterotetrameric adaptor complexes such as AP-1, AP-2, AP-3, and AP-4, which later bind GGA adaptor proteins (4, 147, 148, 190192). …”
Section: Modulation Of Receptor Trafficking and Sequestration By Smentioning
confidence: 99%
“…Interestingly, 87-LL is part of a larger motif that is precisely conserved in the EGFR (26), suggesting its involvement in cargo selection and/or targeting EGFRs to lysosomes. This conjecture is supported by evidence that this sequence in the EGFR is necessary for ligand-induced trafficking to lysosomes (32,33) and also RID␣-mediated diversion of recycling EGFRs to lysosomes (44). Thus, although 87-LL may not be directly involved in AP recognition, it undoubtedly has an important role in RID␣ function at least as it relates to EGFR downregulation.…”
Section: Discussionmentioning
confidence: 92%
“…Stable NR6 cell lines expressing human wild-type EGFRs or receptors with 679-LL converted to 679-AA are described elsewhere (Kil et al, 1999;Kil and Carlin, 2000;Tsacoumangos et al, 2005). Individual clones with matched levels of expression were selected by sterile cell sorting by flow cytometry after cells were stained with a human-specific EGFR antibody.…”
Section: Methodsmentioning
confidence: 99%
“…As EGFR recycling is known to be relatively slow compared to internalization (approximately 15 min versus 4-5 min, respectively) (Wiley, 2003), the net effect of the 679-AA mutation is to increase the pool of receptors in early endosomes compared to wild-type receptors. We have also demonstrated that 679-LL is an a-helical stabilizing motif, distinguishing it from other dileucine-based sorting signals with obligatory aminoterminal acidic residues that are recognized in the form of an extended b or b-like conformation and suggesting that it has a novel mode of action (Bonifacino and Traub, 2003;Tsacoumangos et al, 2005). Furthermore, EGFRs with a mutated 679-AA sequence interact with c-Cbl and undergo protein ubiquitination suggesting this protein modification is not sufficient for EGFR downregulation Tsacoumangos et al, 2005).…”
Section: Introductionmentioning
confidence: 91%